Prediksi Financial Distress pada Perusahaan Credit Suisse Group AG Periode 2013-2022 - Lidyana Syaputri; M Yusuf; Afrizawati M; Hendra Sastrawinata (Politeknik Negeri Sriwijaya, 2024)
The purpose of this study is to find out if Credit Suisse Group AG companies experience financial distress or are healthy companies using the Grover (G-Score) method in the period 2013 – 2022. Credit Suisse companies are companies engaged in banking services. The type of data used as the focus of this research is quantitative which is based on the financial statements of Credit Suisse Group AG for the period 2013 to 2022. And the analysis variable used is the Grover method approach (G-Score). The results of the study can be concluded that the Credit Suisse Group AG company in the 2020-2022 period is in the category of an unhealthy company (Financial Distress) with the result of each negative Grover ratio, the G value is smaller than -0.02. The company will certainly experience financial problems or financial distress for the next few years, this is caused by the company's debt which continues to increase every year. And also the company's debt has exceeded the company's current assets so that the value of the company's working capital is at a negative value. For further research, it is recommended to add other financial distress method variables so that the research results are more accurate.